Serum osteopontin levels in patients with psoriasis vulgaris and its relation with oxidative stress - Cem Kılınç; Selma Korkmaz; Gülben Sayılan Özgün; Sezin Fıçıcıoğlu; Süleyman Pişkin (Galenos Publishing House, 2023)
Background and Design: Oxidative stress is known to play a role in the etiopathogenesis of psoriasis. Recent data suggest that osteopontin (OPN) can also play a role in the pathogenesis of psoriasis. In the current study, OPN levels and oxidative stress were evaluated in patients with psoriasis. Materials and Methods: The study included 61 patients with psoriasis and 62 healthy controls. The OPN levels, total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI) were measured using serum. The disease severity was evaluated using the psoriasis area and severity index (PASI). Results: No statistically significant differences in OPN, TAS, and OSI values were identified between the psoriasis and control groups. A negative correlation was found with the TAS. There was no statistically significant correlation between the PASI score and OPN, TAS, TOS, and OSI values. Conclusion: We did not find a statistically significant correlation between OPN levels and oxidative stress in patients with psoriasis. We believe that larger and more detailed studies are needed to highlight the role of OPN and oxidative stress in the etiopathogenesis of psoriasis.